Kualitas Layanan Dan Kepuasan Pelanggan Terhadap Aksesibilitas Aplikasi Pln Mobile : Sebuah Telaah Literatur - Desmon Saing; Suryanto Suryanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research explores the relationship between Service Quality and Customer Satisfaction with Accessibility in the PLN Mobile Application. This study discusses in detail the benefits of the PLN Mobile Application to support the PT PLN (Persero) Transformation program through big aspirations, one of which is Customer Focus. PLN Mobile is a PLN electricity service application for customers (Mobile Customer Self Service) which is integrated with the Integrated Complaints and Complaints Application (APKT) and the Centralized Customer Service Application (AP2T) where the PLN Mobile application can be downloaded via the Play Store and App Store. PT PLN has continuously provided feature updates and various other services to customers since this application was launched, until now the PLN Mobile Application has been used for more than 3 (three) years and has been downloaded by more than 10 (ten) million downloaders with a Rating Stars 4.8 out of 5 Scale (01/29/2024). This study synthesizes the results through several case studies where the emphasis on the importance of transformation carried out by PLN is through the development of the PLN Mobile application. The discussion was held to describe the practicalities and see the influence that occurred from the development of the application and to convey the obstacles found from this literary study and to provide recommendations for further research including exploring the accessibility of the PLN Mobile application to improve Service Quality and Customer Satisfaction. Keywords: Service Quality & Customer Satisfaction; PLN Mobile.